S105 Pulmonary fibroblasts display conserved damage response phenotypes following sterile and viral injury. (11th November 2022) - Worrell, JC; Finney, GE; Hargrave, KE; Hansell, C; Nijjar, JS; Morton, F; Cole, J; Jackson, MR; Stevenson, K; Chahal, SK; Curely, E; Quintana, RG; et al.
Abstract : Introduction and Objectives: Pulmonary fibroblasts respond to environmental signals triggered by injury or infections, shaping subsequent responses in the lung. Fibroblasts may contribute to enhanced immune protection, or chronic pathogenic inflammation and fibrosis. We hypothesise that molecules upregulated by lung fibroblasts early following influenza A virus (IAV) infection and bleomycin-induced injury persist, in order to generate/maintain immune memory, via altered stromal-immune cell communication. Methods: To address this, we performed RNA-seq on FACS sorted lung fibroblasts from naïve animals and at early (day 10) and late time points (day 40) following intranasal IAV infection. Transcriptional changes were compared with the bleomycin model of early lung injury (publicly available RNA-seq). The functional profile and location of injury altered lung stromal and immune cells was determined using flow cytometry and immunohistochemistry. Results: Analysis of differentially expressed genes demonstrated an enrichment in cell cycle and extracellular matrix genes at day 10 post IAV infection (FDR < 0.05), consistent with fibroblast activation profiles in the bleomycin-injured lung. Three distinct lung fibroblast populations were identified using flow cytometry: damage-responsive (DRF), interferon-responsive (IRF), and antigen-presenting fibroblasts (APF). DRF were significantly elevated in both models at day 10 post injury, while IRF were only detectable in the IAV lung. Interestingly, APF were reduced in the bleomycin lung compared to naïve controls. Furthermore, immunohistochemistry demonstrated that expression of the immunomodulatory molecule, podoplanin, was found in close proximity to immune cell infiltrates in the lung in both models. Conclusions: These data have important implications for understanding the altered communications between immune and stromal cells during and following subsequent lung infections and injury/fibrotic responses.